Charcot spinal arthropathy: an increasing long-term sequel after spinal cord injury with no straightforward management - Grassner, Lukas (Spinal Cord Ser Cases, 2015)
Charcot spinal arthropathy (CSA) is most likely increasing in patients suffering from consequences of spinal cord injury. We want to highlight initial symptoms, certain risk factors and perioperative complications of this condition. A single center retrospective case series in a specialized Center for Spinal Cord Injuries, BG Trauma Center Murnau, Germany highlighting the potential obstacles in the management of Charcot spine. We describe four female paraplegic patients (mean age: 50.75 years; range: 42–67), who developed Charcot spinal arthropathies. The mean age at the time of the accident was 21.5 years (3–35), the time lag after the accident before CSA was developed and finally diagnosed was on average 29.5 years (17–39) and the mean follow-up period was 39.5 months (6–73). Patient histories, initial symptoms, risk factors as well as the management and postoperative complications are provided. Charcot spine is an important potential sequel of spinal cord injury, which can lead to significant disability and spinal emergencies in affected individuals. More studies are needed to provide better recommendations for spine surgeons. Conservative treatment is an option. Posterior fixation alone does not seem to be sufficient.